Usability evaluation of a community-led innovation mobile app - Branco, André Castello (2022)
Digital media can facilitate collaborative processes among local agents, value endogenous resources, and promote assets associated with territory. This article presents the results of a study concerning the development and validation of a mobile app for promoting the relationship among agents of the Portuguese Centro region’s communities/entities. This paper focuses on the results of a heuristic evaluation of the mobile app carried out with two groups of experts in Digital Technologies, Tourism, Health, and Well-Being, besides providing an overview of the mobile app that was developed and a theoretical background regarding community-led innovation, usability, and heuristics. For the CeNTER app prototype evaluation itself, the use of Nielsen's heuristics, a MATCH-MED scale, together with a Think-Aloud Protocol allowed us to improve its usability. This article contributes to a reflection about the evaluation of mobile apps in the scope of territorial-based innovation initiatives, engaging its stakeholders in the process.